El español en los Andes durante la evangelización del Perú colonial desde la perspectiva académica alemana - Huamanchumo de la Cuba, Ofelia (2012)
This article presents an account of the research and publications done by philologists and academic researchers from German universities around the Spanish in the Andes —one of its varieties is the «Andean Spanish»— at the stage of the evangelization of Peru in the sixteenth and seventeenth centuries, which is the topic and the time frame of the topics reviewed articles that comprise this Dossier. Here will be presented in summary form: the evolution of interest in the themes about the Spanish in America; the promoted methods; the different perspectives adopted; and finally, the main contributions of the more recent studies.